Investigation of an MAA Test With Virtual Sound Synthesis - Meng, Ruijie; Xiang, Jingpeng; Sang, Jinqiu; Zheng, Chengshi; Li, Xiaodong; Bleeck, Stefan; Cai, Juanjuan; Wang, Jie (Frontiers in Psychology, 2021)
The ability to localize a sound source is important in our daily life, specifically to analyze auditory scenes in complex acoustic environments. The concept of minimum audible angle (MAA), which is defined as the smallest detectable difference between the incident directions of two sound sources, has been widely used in the research fields of auditory perception to measure localization ability. Measuring MAAs usually involves a reference sound source and either a large number of loudspeakers or a movable sound source in order to reproduce sound sources at a large number of predefined incident directions. However, existing MAA test systems are cumbersome because they require many loudspeakers or a mechanical rail slide and thus are expensive and inconvenient to use. This study investigates a novel MAA test method using virtual source synthesis . We compare the perceptual localization acuity of sound sources in two experimental designs: using the virtual presentation and real sources. The virtual sound source is reproduced through a pair of loudspeakers weighted by vector-based amplitude panning (VBAP). Results show that the average measured MAA at 0◦ azimuth is 1.14◦ and the average measured MAA at 90◦ azimuth is 3.07◦ in a virtual acoustic system, meanwhile the average measured MAA at 0◦ azimuth is about 1.16◦ and the average measured MAA at 90◦ azimuth is 3.29◦ when using the real sources. The measurements of the two methods have no significant difference. We conclude that the proposed MAA test system is a suitable alternative to more complicated and expensive setups.